SUBSTITUTION OF FLOUR SEA GRAPES Caulerpa racemosa FERMENTED ON TILAPIA (Oreochromis niloticus) FEED - Lumbessy, Salnida Yuniarti (MARLIN, 2025)
The purpose of this study was to analyze the effect of substitution of C. racemosa fermented sea grape flour in the feed formulation on tilapia. This research was conducted at the Laboratory of Fish Production and Reproduction, University of Mataram for 50 days from March-May 2022. This study used an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The treatments tested were control (P1), 4% fermented sea grape flour (P2), 8% fermented sea grape flour (P3), and 12% fermented sea grape flour (P4). Data were analyzed using analysis of variance (ANOVA) at 5% level with 95% confidence interval and continued with Duncan's test. The results showed that the average absolute weight of fish for 50 days of rearing mass with artificial feeding and at various concentrations of fermented C. racemosa sea grape flour ranged from 9.43-11.58 g, absolute length ranged from 2.24-2 .90 cm, and the specific growth rate ranged from 2.36 to 2.64%/day. Then for the efficiency of feed utilization (EPP ranges from 76.8-95.8%, feed conversion ratio (FCR) ranges from 1.05-1.31 and survival (SR) ranges from 90-97%. Conclusions from this study that the addition of the concentration of fermented C. racemosa sea grape flour can affect the absolute weight of tilapia, but does not affect the absolute length, specific growth rate, FCR value, feed efficiency, and survival rate. 4% (P2) gave the best result because it could increase the absolute weight of tilapia by 11.58 g